Economic Impact of Culinary Tourism Center Management - Andi Abriani (Journal of Social Commerce, 2022)
There are inconsistencies in the purchase and selling of tourist items that have not been formally organized by the government. However, tourist objects have an effect on the community by allowing them to increase their income via small enterprises. Using qualitative descriptive research and a phenomenological research technique, this study tries to investigate the process of developing a tourist attraction and the socioeconomic effect of the Wajo Regency tourist attraction. Using three methods to collect data for this study: observation, interviews, and documentation. The findings demonstrated that the presence of the Wajo Regency tourist attraction might allow a small company to turn a new page in terms of raising their daily revenue. The community members who are actively engaged in the creation of the Wajo Regency tourist attraction have a social influence on the surrounding community's attitude towards the environment. Tourism in the Wajo Regency may have both beneficial and bad effects on the local people.